Growth patterns and cardiovascular abnormalities in SGA fetuses: 2. Normal growth and progressive growth restriction. (18th July 2022) - Deter, Russell L.; Dicker, Patrick; Lee, Wesley; Tully, Elizabeth C.; Cody, Fiona; Malone, Fergal D.; Flood, Karen M.
Abstract: Objectives: To characterize growth processes and their associated cardiovascular abnormalities in SGA fetuses with normal growth and progressive growth restriction patterns as defined by Individualized Growth Assessment (IGA). Methods: A SGA cohort (EFW and BW < 10th percentile) was derived from the PORTO study that included 47 fetuses with normal growth outcome (SGA Normal) and 34 fetuses with progressive growth restriction (SGA Growth Restricted, Pattern 1). Composite fetal size parameters were used to quantify growth pathology at individual third trimester time points (individual composite Prenatal Growth Assessment Score {icPGAS}) and calculated cumulatively during the third trimester (Fetal Growth Pathology Score 1FGPS1). Paired Doppler evaluations of the umbilical artery (UA), middle cerebral artery (MCA), ductus venosus (DV) and myocardial performance index (MPI) were used to detect cardiovascular anomalies. Outcome variables were birth age and birth weight. Results: Ranking fetuses with respect to the severity of the 3rd trimester growth pathology (–FGPS1) revealed three subgroups in each of these two groups. In SGA Normal, no (51%), minimal (19%) or minor (30%) growth abnormalities were present. Although vascular flow abnormalities occurred without growth abnormalities (UA: 38%; MCA: 35%), they increased with minor growth disturbances (UA: 64%; MCA: 50%). All fetuses delivered at term and in only 7 cases (minor growth abnormalities subgroup) were the neonates abnormally small based on IGA criteria. In SGA Growth Restricted, Pattern 1, the progression of growth restriction was slow (47%), moderate (21%) and rapid (32%). Corresponding median –FGPS1 values were −1.34%, −2.67% and −4.88%, respectively. The median age of onset was 33.6, 29.7 and 29.7 weeks in these three subgroups. UA abnormalities occurred infrequently in the first two subgroups but were found in all cases of rapidly progressing pathology. Similar results were found for the MCA and DV + MPI Doppler parameters (rapid progression: MCA = 50%; DV + MPI = 50%). Premature delivery occurred less frequently with slow progression but was nearly 100% in the moderately and rapidly progressive subgroups. Conclusions: Negative FGPS1 growth restriction patterns can be used to classify SGA fetuses. Subgroups, based on ranked –FGPS1 values in both SGA Normal and SGA Growth Restricted Pattern 1 groups had marked differences in cardiovascular abnormalities and neonatal outcomes. The characteristics of these two groups are consistent with small, normally growing fetuses and fetuses with "early" growth restriction, respectively.